Bioactive Neuroelectronic Interfaces - Adewole, Dayo O.; Serruya, Mijail D.; Wolf, John A.; Cullen, D. Kacy (Frontiers in Neuroscience, 2019)
Within the neural engineering field, next-generation implantable neuroelectronic interfaces are being developed using biologically-inspired and/or biologically-derived materials to improve upon the stability and functional lifetime of current interfaces. These technologies are based around biomaterials, bioactive molecules, living cells, or some combination of these to promote host neuronal survival, reduce the foreign body response, and/or improve chronic device-tissue integration. This article provides a general overview of the different strategies, milestones, and evolution of such bioactive neural interfaces including electrode material properties, biological coatings, and “decoration” with living cells. Another such biohybrid approach developed in our lab uses preformed implantable micro-tissue featuring long-projecting axonal tracts encased within carrier biomaterial micro-columns. These so-called "living electrodes" have been engineered with carefully tailored material, mechanical, and biological properties to enable natural, synaptic based modulation of specific host circuitry while ultimately being under computer control. This article provides an overview of these axon-based living electrodes, including design and fabrication, performance attributes, as well as findings to date characterizing in vitro and in vivo functionality.